Research progress on the role of ferroptosis in cardiovascular disease - Li, Han; Lin, Li; Xia, Yun-Long; Xie, Yunpeng; Yang, Xiaolei (Frontiers in Cardiovascular Medicine, 2022)
The cardiovascular disease pathogenesis is extremely complex and seriously threatens human health. Cardiomyocyte death plays a significant role in cardiovascular disease occurrence and development. In addition to the previously revealed modes of cell death (apoptosis, autophagy, and pyroptosis), ferroptosis is highly related to the development of cardiovascular diseases, including arrhythmia, atherosclerosis, and myocardial ischemia/reperfusion. Ferroptosis is a novel cell death pathway driven by lipid peroxidation and iron overload. Lipid, amino acid, and iron metabolism regulate the ferroptosis pathway. Small molecule compounds (iron chelators, antioxidants, and ferroptosis inhibitors) and genetic programming can alleviate or prevent cardiovascular disease by inhibiting the ferroptosis pathway. Ferroptosis plays a key role in various cardiovascular disease occurrence and development, and inhibiting ferroptosis in cardiomyocytes is expected to become a feasible treatment method. In this Mini-Review, we systematically summarize the molecular mechanisms of ferroptosis in different cardiovascular diseases, delineate the regulatory network between ferroptosis and cardiovascular diseases, and highlight its potential therapeutic targets.